Early Start Preschool Politics in the United States - Karch, Andrew (University of Michigan Press, 2013)
In the United States, preschool education is characterized by the dominance of a variegated private sector and patchy, uncoordinated oversight of the public sector. Tracing the history of the American debate over preschool education, Andrew Karch argues that the current state of decentralization and fragmentation is the consequence of a chain of reactions and counterreactions to policy decisions dating from the late 1960s and early 1970s, when preschool advocates did not achieve their vision for a comprehensive national program but did manage to foster initiatives at both the state and national levels. Over time, beneficiaries of these initiatives and officials with jurisdiction over preschool education have become ardent defenders of the status quo. Today, advocates of greater government involvement must take on a diverse and entrenched set of constituencies resistant to policy change.